MiR-21-5p Induces Pyroptosis in Colorectal Cancer via TGFBI - Jiang, Rilei; Chen, Xiaolei; Ge, Shaohua; Wang, Qin; Liu, Yichang; Chen, Haijun; Xu, Jiatuo; Wu, Jiang (Frontiers in Oncology, 2021)
Pyroptosis is a distinct form of programmed cell death in eukaryotic cells that has garnered increasing attention in cancer-related research. Moreover, although miR-21 has been reported as abnormally expressed in colorectal cancer, due to a lack of in-depth research on the transcriptional regulation mechanisms of miR-21, its clinical usage remains limited. Our study is the first, to our knowledge, to compare the clinical manifestations and laboratory phenotypes associated with miR-21-3p and miR-21-5p. Morphologically, the transfection of miR-21-3p or miR-21-5p inhibitors, as well as miR-21-5p mimics into HCT-116 and HT-29 cell lines, induced cell death. Surprisingly, overexpression of miR-21-5p induced cell death more strongly than its knockdown. Mechanistic studies of miR-21-5p overexpression revealed that various inflammatory factors including IL-1β and IL-18 were released, while pyroptosis-associated mRNAs were upregulated and proteins were activated. Moreover, miR-21-5p was found to act as a downstream factor to significantly and directly regulate transforming growth factor beta-induced (TGFB1). Specifically, miR-21-5p overexpression caused downregulation of TGFBI, which may have led to pyroptosis. Collectively, we revealed that miR-21-5p induces pyroptosis in colorectal cancer via TGFBI regulation, thereby providing important mechanistic insights into its antitumor effects and expanding its potential for clinical applications.